2020
DOI: 10.3389/fnins.2020.00507
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Dysregulated MicroRNAs in Myasthenia Gravis

Abstract: Myasthenia gravis (MG) is a rare acquired autoimmune neuromuscular disease. Autoantibodies, cellular immunity, complement, and cytokines are involved in the pathogenesis of MG. It is characterized by the dysfunction of neuromuscular junction transmission and skeletal muscle weakness. MicroRNAs (miRNAs) are non-coding small molecule ribonucleic acids that regulate various biological processes (e.g., development, differentiation, and immunity) at the transcriptional and post-transcriptional levels of gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 85 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…We also identified the miRNA pathway in cancer. An increasing number of studies have suggested that miRNAs are involved in the occurrence and development of MG [ 39 ]. The miRNA profile of peripheral blood from MG patients was sequenced using a next-generation sequencing approach, and 41 miRNAs were found to be differentially expressed in nonresponders versus responders to immunosuppressive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified the miRNA pathway in cancer. An increasing number of studies have suggested that miRNAs are involved in the occurrence and development of MG [ 39 ]. The miRNA profile of peripheral blood from MG patients was sequenced using a next-generation sequencing approach, and 41 miRNAs were found to be differentially expressed in nonresponders versus responders to immunosuppressive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike AChR and MuSK antibodies, Lrp4 and agrin antibodies are rare in MG, resulting in limited research on these subgroups. Although some miRNAs have been identified as potential regulators of Lrp4 or agrin (82)(83)(84)(85)(86)(87)(88), the precise relationship between miRNAs and these two antibodies remains undiscovered (89).…”
Section: Mirnas Intertwined With Musk-mgmentioning
confidence: 99%